Australian and New Zealand recommendations for the diagnosis and management of gout: integrating systematic literature review and expert opinion in the 3e Initiative. (17th April 2015) - Graf, Scott W.; Whittle, Samuel L.; Wechalekar, Mihir D.; Moi, John H. Y.; Barrett, Claire; Hill, Catherine L.; Littlejohn, Geoff; Lynch, Nora; Major, Gabor; Taylor, Andrew L.; Buchbinder, Rachelle; Zochling, Jane
Abstract Aim To develop evidence‐based recommendations for the diagnosis and management of gout in Australia and New Zealand as part of the multi‐national 3e Initiative. Method Using a formal voting process, a panel of 78 international rheumatologists selected 10 key clinical questions pertinent to the diagnosis and management of gout. An additional question was also developed by participating Australian and New Zealand rheumatologists. Each question was investigated with a systematic literature review. MEDLINE, EMBASE, Cochrane CENTRAL and abstracts from 2010 to 2011 European League Against Rheumatism and American College of Rheumatology meetings were searched in each review. Relevant studies were independently reviewed by two individuals for data extraction and synthesis and risk of bias assessment. Using this evidence, 47 Australian and New Zealand rheumatologists developed national recommendations. For each recommendation the level of agreement was assessed and the level of evidence graded. Result Eleven recommendations were produced relating to the diagnosis of gout, different aspects of the management of gout, cardiovascular and renal comorbidities and the management of asymptomatic hyperuricemia. The mean level of agreement with the recommendations was 9.1 on a 1–10 scale, with 10 representing full agreement. Conclusion Eleven Australian and New Zealand recommendations on the diagnosis and management of gout were developed combining systematically reviewed evidence with local expertise, enhancing their utility in clinical practice.